Researching teacher educators' preparedness to teach to and about diversity: investigating epistemic reflexivity as a new conceptual framework. Issue 3 (27th May 2019) - Lunn Brownlee, Jo; Rowan, Leonie; Ryan, Mary; Walker, Sue; Bourke, Terri; Churchward, Peter
ABSTRACT: There is growing international concern about the extent to which teachers are prepared to work with an increasingly diverse student (and community) population. To date, research into the relationship between teacher preparation and preparedness to teach diverse learners has not focused on teacher educators' understandings about teaching to/about diversity. Such understandings can be informed by epistemic aspects of professional work. Epistemic cognitions (cognitions about knowledge and knowing) allow professionals to generate perspectives necessary to tackle new and old challenges. The social lab reported in this paper investigated 12 Australian teacher educators' perspectives about teaching to/about diversity using the 3R-Epistemic Cognition (EC) framework. The findings showed that the 3R-EC framework could be useful for capturing epistemic reflexive dialogues about teaching to/about diversity, although some aspects of the framework were identified by the teacher educators as challenging. On the basis of these identified challenges, refinements concerning communication and use of the 3R-EC framework were identified. The feedback also led to some refinements of the social lab methodology for use in the larger national study.